Taxonomy of tepary bean and wild relatives as determined by amplified fragment length polymorphism (AFLP) markers - Muñoz Flórez, Ligia Carmenza; Duque E., Myriam Cristina; Debouck, Daniel G.; Blair, Matthew W. (Wiley, 2006)
Tepary bean (Phaseolus acutifolius A. Gray), a low-rainfall crop from the Sonoran desert, is thought to have low diversity; however, its relationship to its wild relatives is poorly understood. In this study, a total of 147 accessions were evaluated by means of AFLP markers to (i) establish the taxonomic relationships within and between the Acutifolii and other sections and (ii) to understand tepary bean domestication. The structure among the 10 species analyzed corresponded to currently recognized sections: Phaseolus glabelus and Phaseolus lunatus L. were equally distant from the phaseoli and coccinei sections and the rugosi section included Phaseolus angustissimus, Phaseolus carteri and Phaseolus filiformis We also compared the gene pool differences for common (Phaseolus vulgaris L.) and lima bean (P. lunatus) with differences observed within the Acutifolii section. The wild relative, Phaseolus parvifolius persistently separated from the bulk of both cultivated and wild tepary, validating its status as a separate species; while within the wild accessions, there was no obvious grouping along the foliar variants. On the basis of our results, one of two Mexican states, Sinaloa or Jalisco, could have been the domestication center, although the hypothesis of multiple domestication events cannot be discarded. Furthermore, domesticated tepary bean was most likely derived from wild genotypes of var. acutifolius rather than genotypes of var. tenuifolius.